Oncocytoma of the Parotid Gland with Facial Nerve Paralysis - Seijiro Hamada; Keishi Fujiwara; Hiromitsu Hatakeyama; Akihiro Homma (Case Reports in Otolaryngology)
Parotid gland tumor with facial nerve paralysis is strongly suggestive of a malignant tumor. However, several case reports have documented benign tumors of the parotid gland with facial nerve paralysis. Here, we report a case of oncocytoma of the parotid gland with facial nerve paralysis. A 61-year-old male presented with pain in his right parotid gland. Physical examination demonstrated the presence of a right parotid gland tumor and ipsilateral facial nerve paralysis of House–Brackmann (HB) grade III. Due to the facial nerve paralysis, a malignant tumor of the parotid gland was suspected and right parotidectomy was performed. Oncocytoma was confirmed histopathologically. The facial nerve paralysis was resolved 2 months after surgery. During the follow-up period (one and a half years), no recurrence was observed. As the tumor showed a distinctive dumbbell shape and increased somewhat due to inflammation (i.e., infection), the facial nerve was pinched by the enlarged tumor. Ischemia and strangulation of the nerve were considered to be the cause of the facial nerve paralysis associated with the benign tumor in this case.